The use of surface electromyography in biomechanics - De Luca, C. J. (Journal of Applied Biomechanics, 1997)
This lecture explores the various uses of surface electromyography in the field of biomechanics. Three groups of applications are considered: those involving the activation timing of muscles, the force/EMG signal relationship, and the use of the EMG signal as a fatigue index. Technical considerations for recording the EMG signal with maximal fidelity are reviewed, and a compendium of all known factors that affect the information contained in the EMG signal is presented. Questions are posed to guide the practitioner in the proper use of surface electromyography. Sixteen recommendations are made regarding the proper detection, analysis, and interpretation of the EMG signal and measured force. Sixteen outstanding problems that present the greatest challenges to the advancement of surface electromyography are put forward for consideration. Finally, a plea is made for arriving at an international agreement on procedures commonly used in electromyography and biomechanics. Betrachtet werden drei Gruppen des EMG-Einsatzes in der Biomechanik: 1. die Gruppe der Applikationen, bei der es um das Aktivierungstiming der Muskeln geht, 2. bei der es um die Beziehung der Kraft zum EMG-Signal geht und 3. bei der es um die Nutzung des EMG-Signals als Ermüdungskennzeichen geht. Es wird auch darübwer diskutiert, wie EMG-Signale mit maximaler Genauigkeit aufgezeichnet werdem können, und es wird ein Kopmendium aller bekannter Faktoren vorgestellt, die die im EMG-Signal enthaltenen Informationen beeinflussen. Es werden 16 Empfehlungen für den adäquaten EMG-Einsatz ausgesprochen wie auch eine gleiche Anzahl von Problembereichen angesprochen wird, die in der Zukunft zur Lösung noch anstehen. - gekürztes Autorreferat -